Isoptericola halalbus sp. nov., a halotolerant actinobacterium isolated from saline lake sediment. Issue 8 (20th August 2020) - Ming, Hong; Niu, Ming-ming; Cheng, Li-jiao; Zhang, Yan-min; Yi, Bing-fang; Xia, Ting-ting; Li, Meng; Nie, Guo-Xing
Abstract : A novel Gram-stain-positive bacterium, designated CFH 91151 T, was isolated from sediment collected from a saline lake in Yuncheng, Shanxi Province, PR China. Cells of strain CFH 91151 T were rod-or v-shaped, aerobic, non-motile, non-spore-forming and halotolerant. Results of 16S rRNA gene sequence analysis revealed that strain CFH 91151 T was closely related to Isoptericola variabilis MX5 T and Isoptericola nanjingensis H17 T (98.7 and 98.4% sequence similarity, respectively). The strain grew at 4–45 °C, pH 5.0–9.0 and with 0–14.0 % (w/v) NaCl. Cells were positive for catalase, nitrate was not used and H2 S was not produced. Major cellular fatty acids were anteiso-C15 : 0 (62.76 %), anteiso-C17 : 0 (12.09 %) and iso-C15 : 0 (9.46 %). The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol, phosphatidylinositol, two unidentified phospholipids and three unidentified glycolipids. The menaquinone was MK-9 (H4). The genome size was 4.10 Mbp with a G+C content of 72.4 mol%. The average amino acid identity (ANI) and in silico DNA–DNA hybridization (DDH) values between CFH 91151 T and the other species of the genus Isoptericola were found to be low (ANIm <87.19 %, ANIb <84.38 % and DDH <29.30 %). Based on physiological properties, chemotaxonomic characteristics and low ANI and DDH results, strain CFH 91151 T is considered to represent a novel species, for which the name Isoptericola halalbus sp. nov. is proposed. The type strain is CFH 91151 T (=DSM 105976 T =KCTC 49061 T ).